Circulating levels of micronutrients and risk of infections: a Mendelian randomization study - Helene M. Flatby; Anuradha Ravi; Jan K. Damås; Erik Solligård; Tormod Rogne (BMC Medicine, 2023)
Abstract Background Micronutrients play an essential role at every stage of the immune response, and deficiencies can therefore lead to increased susceptibility to infections. Previous observational studies and randomized controlled trials of micronutrients and infections are limited. We performed Mendelian randomization (MR) analyses to evaluate the effect of blood levels of eight micronutrients (copper, iron, selenium, zinc, beta-carotene, vitamin B12, vitamin C, and vitamin D) on the risk of three infections (gastrointestinal infections, pneumonia, and urinary tract infections). Methods Two-sample MR was conducted using publicly available summary statistics from independent cohorts of European ancestry. For the three infections, we used data from UK Biobank and FinnGen. Inverse variance-weighted MR analyses were performed, together with a range of sensitivity analyses. The threshold for statistical significance was set at P < 2.08E−03. Results We found a significant association between circulating levels of copper and risk of gastrointestinal infections, where a one standard deviation increase in blood levels of copper was associated with an odds ratio of gastrointestinal infections of 0.91 (95% confidence interval 0.87 to 0.97, P = 1.38E−03). This finding was robust in extensive sensitivity analyses. There was no clear association between the other micronutrients and the risk of infection. Conclusions Our results strongly support a role of copper in the susceptibility to gastrointestinal infections.